Scalable light field coding with support for region of interest enhancement - Conti, C. (2018)
Light field imaging based on microlens arrays - a.k.a. holoscopic, plenoptic, and integral imaging - has currently risen up as a feasible and prospective technology for future image and video applications. However, deploying actual light field applications will require identifying more powerful representation and coding solutions that support emerging manipulation and interaction functionalities. In this context, this paper proposes a novel scalable coding approach that supports a new type of scalability, referred to as Field of View (FOV) scalability, in which enhancement layers can correspond to regions of interest (ROI). The proposed scalable coding approach comprises a base layer compliant with the High Efficiency Video Coding (HEVC) standard, complemented by one or more enhancement layers that progressively allow richer versions of the same light field content in terms of content manipulation and interaction possibilities, for the whole scene or just for a given ROI. Experimental results show the advantages of the proposed scalable coding approach with ROI support to cater for users with different preferences/requirements in terms of interaction functionalities.